Effectiveness of ertapenem for treatment of infections in children: An evidence mapping and meta-analysis - Ruiqiu Zhao; Xiaoru Long; Jiangxia Wang; Jing Zhu; Cong Liu; Tingting Shang; Zhenzhen Zhang; Engels Obi; Lynda Osadebe; Yue Kang; Jie Liu; Xiaodi Chen; et al. (Frontiers Media S.A., 2022)
ObjectivesTo assess and summarize current evidence on the effectiveness and safety of ertapenem for treatment of childhood infections, in consideration of high infection prevalence in children and wide use of ertapenem.MethodsThe following 8 databases were searched on 13th May 2021: Web of Science, Embase via Ovid SP, PubMed, The Cochrane Library (CENTRAL), Chinese BioMedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), VIP and Wanfang. The primary outcome was treatment success rate. Risk ratios (RRs) and 95% confidence interval (CI) were estimated using random-effect models. Subgroup analysis was conducted where heterogeneity was found.ResultsFifteen studies (8 randomized controlled trials, 1 observational comparative study, and 6 before and after studies) involving 2,528 patients were included in the final review. Ertapenem had similar treatment success rates with β-lactam antibiotics [relative risk (RR) = 1.08, 95% CI: 0.99-1.19]. In a subgroup analysis, similar efficacy (RR = 1.08, 95% CI: 0.97-1.20) between ertapenem and other carbapenems. Compared with β-lactam antibiotics, ertapenem did not increase the risk of any adverse events (RR = 1.02, 95%CI: 0.71-1.48), drug-related diarrhea (all non-Asian children, RR = 0.62, 95%CI: 0.31-1.25), or injection site pain (all non-Asian children, RR = 1.66, 95%CI: 0.59-4.68). Subgroup analysis showed no obvious difference between ertapenem group and carbapenems or non-carbapenems group on risk of adverse events.ConclusionOur findings suggest that ertapenem is effective and safe in treatment for children with infection. Further comparative real-world data is needed to supplement clinical evidence on the overall benefits of ertapenem in this population.